Analysis of Tumor Glycosylation Characteristics and Implications for Immune Checkpoint Inhibitor’s Efficacy for Breast Cancer - Lv, Wenchang; Yu, Honghao; Han, Mei; Tan, Yufang; Wu, Min; Zhang, Jun; Wu, Yiping; Zhang, Qi (Frontiers in Immunology, 2022)
The alterations of glycosylation, which is a common post-translational modification of proteins, have been acknowledged as key events in breast cancer (BC) oncogenesis and progression. The aberrant expression of glycosyltransferases leads to aberrant glycosylation patterns, posing the diagnostic potential in BC outcomes. The present study aims to establish a glycosyltransferases-based signature to predict BC prognosis and response to immune checkpoint inhibitors. We firstly screened 9 glycosyltransferase genes from the TCGA database, and accordingly constructed a glyco-signature to predict the prognosis of BC patients. Depending on the median cutoff of the risk score in this signature, the BC patients were successfully divided into high- and low-risk groups. Next, the combinational analyses of uni- and muti-Cox regression, Kaplan-Meier, and ROC curves were used to prove that this glyco-signature possessed excellent predictive performance for prognosis of BC patients, as the high-risk group had worse outcomes compared with the low-risk group. Additionally, the GSEA and immunologic infiltration analysis were adopted and indicated that there was a more immunosuppressive state in the high-risk group in comparison to the low-risk group. The clinical sample validation verified that glycosyltransferase genes were differentially expressed in patients with different risks, while the biomarkers of anti-tumor M1 macrophages were increased and N-glycosyltransferase STT3A decreased in the low-risk group. The final in vitro assay showed that the silencing of STT3A suppressed the proliferation and migration of BC cells. Collectively, our well-constructed glyco-signature is able to distinguish the high- and low-risk group and accordingly predict BC prognosis, which will synergistically promote the prognosis evaluation and provide new immunotherapeutic targets for combating BC.